Anteseden dan Konsekuensi Kepercayaan Awal terhadap Chatbot - Putri Aryani; Sri Vandayuli Riorini (Peneliti.net, 2023)
Artificial intelligence chatbots are changing the nature of online services by revolutionizing the interaction of service providers with consumers. Thus, this study aims to explore the antecedents (compatibility, perceived ease of use, performance expectancy and social influence) (customer engagement) of chatbot initial trust. A sample of 153 responses was collected in Indonesia using a questionnaire and analyzed using structural equation modeling (SEM) by AMOS 23. The results revealed that except for performance expectancy, all the other four factors (compatibility, perceived ease of use, performance expectancy and social influence) significantly boost customers’ initial trust toward chatbots. Further, initial trust in chatbots encourages customer engagement. The study provides insights into some variables influencing initial chatbot trust. This study suggests key insights for marketing managers on how to build chatbot initial trust, which, in turn, will lead to an increase in customers’ interactions with the brand.